Estado del arte de la tendencia de la ciencia de datos aplicada a la administración de redes de computadores. - Aguirre Lozano, Claudio Vinicio (2018)
This article will show the state of art about data science applied to computational networks. For this work, the analysis was realized by the studies and the applications related, besides, success and fail study cases, theories, guide lines, tools, and so on used to data science. The research question is, if the data science analysis can be used to help to better decisions, by of trending in technological infrastructure that showed in their output data. The scientific methodology is the procedure investigative used essentially in the creation of knowledge based on the science, the same that has been used in this article The results finded showed an increase of measures of output data, especially in nodes of data centers in their internal measures and interactions each other’s. Also, worth highlighting is business applications existed to optimize and centralize information for a better manage by techniques of data science when a millions of data must be evaluated. Finally, one of the results is the growing of data is significant, because by the analysis of many data showed new relationships that before were not be considerated, by example: the CPU temperature and data management to got a better efficiently of power.